Assessment of Phobos gravity field determination from both near polar and near equatorial orbital flyby data. Issue 4 (26th September 2018) - Yan, J G; Yang, X; Ye, M; Andert, T; Jin, W T; Li, F; Jin, S G; Barriot, J P
ABSTRACT: The C20 and C22 coefficients of the Phobos gravity field are key parameters to constrain the internal structure of the Martian moon, but reliable observed values of these parameters are still missing. In this paper, we demonstrate, through a combination of forward and inverse modelling of simulated Doppler spacecraft tracking data collected from the Earth, that a Phobos flyby along a near polar Mars orbit is optimal when determining the C20 coefficient, and further, that a near equatorial flyby Mars orbit is optimal for determination of the C22 coefficient. Therefore, the combination of a near polar and a near equatorial orbit is an effective way to determine the Phobos C20 and C22 gravity field coefficients. This work provides a reference for a future Chinese Mars mission.